2013
DOI: 10.4103/0972-2327.112472
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of migraine in medical students and its impact on their daily activities

Abstract: Background:Migraine is a common neurological disorder with significant impact on quality of life. The aim of this study was to investigate the prevalence and characteristics of migraine headaches in medical students, to measure its impact on their life, and to assess their knowledge about the ailment. Information about lifestyle variables was also collected.Materials and Methods:All medical students who confirmed of having headache for more than 1 year formed the study group. Students filled a detailed questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
52
5
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 38 publications
20
52
5
2
Order By: Relevance
“…Headache has been identifi ed as the predominant indication for medicamentous treatment in many studies [8,[17][18][19][20]. A study conducted in Iran showed that 68% of patients who suff ered from headache had irregular sleeping habits, changing environment Led to a stressful life and in addition, another the predictive factor of headache was poor socio-economic status [21,22]. As self-medication for pain has also been encouraged by the WHO, an appropriate approach to the user will enable safer self-medication and making correct decisions on discomfort elimination largely due to inappropriate administration of medication.. Th e surveyed sample revealed many shortcomings regarding the attitudes and knowledge associated with analgesics use.…”
Section: Resultsmentioning
confidence: 99%
“…Headache has been identifi ed as the predominant indication for medicamentous treatment in many studies [8,[17][18][19][20]. A study conducted in Iran showed that 68% of patients who suff ered from headache had irregular sleeping habits, changing environment Led to a stressful life and in addition, another the predictive factor of headache was poor socio-economic status [21,22]. As self-medication for pain has also been encouraged by the WHO, an appropriate approach to the user will enable safer self-medication and making correct decisions on discomfort elimination largely due to inappropriate administration of medication.. Th e surveyed sample revealed many shortcomings regarding the attitudes and knowledge associated with analgesics use.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of migraine among medical students reported to be 27.9% in Kuwait University (21.4% in males versus 31.1% in females) [3]. The prevalence of Migraine among medical students is 22% in Brazil [4], 12.2% in in Oman [8], 14.1% in Nigeria, 33.8% in Nairobi, 13.1% in South East Nigeria, 12.6% in Turkey, and 7.14% in the Southeast of Iran, and 28% in India [11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…7 The effect of migraine on daily activity of medical students has been studied. 8 Hence, we had attempted to find out the impact of all types of pain on QOL of students. It was found that the pain had an impact on their social life and academics.…”
Section: 6mentioning
confidence: 99%